Siyah bar safīd : Majmūʿa-yi guftārhā u yād dāshthā dar zamīna-yi kitābshināsī u nuskhashināsī - Nawshāhī, ʿĀrif, (Miras Maktoob, ISBN: 9789004365452., 2019)
This is a collection of research notes, personal recollections, interviews with colleagues, and professional letters, sent and received, compiled by the Pakistani specialist of Islamic manuscripts ʿĀrif Nawshāhī (b. 1955). They cover a period of over 35 years of professional activity (1974-2011), mostly in Pakistan, India, and Iran. The work consists of five chapters, of which the research notes contained in chapters one and two are perhaps the most informative ones. Especially interesting is the information on the holdings of some of the libraries in India and Pakistan in chapter one and the codicological notes in chapter two. The notes, memoirs, anecdotes, interviews, and letters of chapters three to five give a fine impression of how this prominent scholar experienced the world of manuscripts and codicologists in which he was active for so many years. And here too, useful information may be found, especially in his long series of very short notes in chapter three.